EMOTIONAL COMPETENCE AND EMOTIONAL INTELLIGENCE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines new approaches to the study of the importance of emotional intelligence and its role in the management activities of a modern manager, analyzes the components of emotional intelligence, describes the peculiarities of the relationship between the level of development of emotional intelligence and the effective and procedural parameters of management activities. The main approaches to the essence and structure of emotional intelligence are systematized. The important role of emotional intelligence development in managerial activity is proved. The dimensions of emotional intelligence in the structure of professional competence of a manager are outlined. The phenomenological level of influence of emotional intelligence on the motivational activity of a manager is noted. The main criteria for the development of emotional intelligence and its impact on the effectiveness of managerial activity are allocated.The effectiveness of today's organizations depends not only on the use of the latest technologies, but also on how skillfully managers unleash the potential of their employees through the development of emotional intelligence. One of the peculiarities of modern organizational activities is that the efficiency of activities and the scale of organizational achievements depend on the level of development of emotional intelligence, especially in the field of management. In this context, questions arise about the development of emotional management, the formation of skills and abilities to assess one's own and subordinates' activities, and the possibility of their mandatory disclosure Numerous studies show a direct relationship between emotional intelligence, personality, and managerial effectiveness. Business leaders are those who have highly developed emotional intelligence, which includes developed self-awareness, self-regulation, empathy, and social skills. These components directly affect the formation of manager-leader motivation.The role of the individual in the modern world is growing very rapidly, as the development of the enterprise and the country's economy as a whole depends on the individual. The harmonious development of the individual, his or her successful social adaptation, and the creation of a favorable social and psychological climate in the team directly affect the motivation and success of the enterprise. It is necessary not only to have professional skills but also to encourage subordinates to develop emotional intelligence in the process of self-realization.It is impossible to turn the process of interaction between management and subordinates into a standard management technology, as it is very complex and difficult to even outline with clearly defined techniques and rules. The manager plays a key role in creating a favorable social and psychological climate. But only a manager with a sufficiently developed emotional intelligence will successfully cope with this task. This is because he or she is able to recognize the moods of subordinates and respond adequately to their reactions and feelings. As a result of such successful interaction, mutual understanding between the manager and subordinates will be achieved.
Keywords: emotional intelligence, emotions, emotional competence, managerial competence.